Beyond the NPT : the evolution of the U.S. non-proliferationpolicy and the nuclearization of Iran in the 1970s - Felci, Vittorio (Études sur la Région Méditerranéenne, 2016)
This article provides new insights into the development of the Iranian nuclear program, by focusing on the political implications of Iran's nuclear cooperation with her Western partners in the 1970s. Using recently declassified documentary evidence from US and European archives, this study will first explore how diversification of nuclear suppliers stemmed not only from the impasse in US-Iran negotiations for a nuclear agreement, but also from a precise strategy of the Shah aimed at avoiding overreliance on the American ally. The article will then examine how nuclear cooperation between Western Europe and Iran challenged the construction of a new US non-proliferation regime, initiated after the Indian nuclear explosion of 1974 in order to amend the inefficiencies of the Nuclear Non- Proliferation Treaty.